The Attributes of Managing Digital and Conventional Marketing by Local Coffee Brand as Antecedent to Consumer Satisfaction - Alverisa, Katarina; Aras, Muhammad; Suparman, Suparman; Qanitah, Tiara (Ridwan Institute, 2024)
This article discusses the strategies for overseeing the marketing communication of a Local Coffee Brand, utilizing both digital and conventional methods. In conventional marketing, Local Coffee Brand use media promotion tools such as banners and word of mouth in their stores. However, there is a limited number of target markets in stores, and Local Coffee Brand uses other digital tools in the promotion. As such, this article aims to shed light on the challenges concerning the use of digital marketing and traditional methods in the Local Coffee Brand industry. To achieve this, content analysis and semi-structured interviews have been utilized to glean comprehensive insights from both the owner and the brand marketing team, all of whom possess significant experience in steering the digital marketing communication strategy. In digital marketing, Local Coffee Brand leverages its application, social media platforms, and website to gain significant advantages. These channels serve as swift and cost-effective tools for marketing communication, particularly in product promotion, advertisement dissemination, and brand awareness. It’s emphasized that managing marketing communication through digital platforms is a strategic approach to inform, persuade, and remind consumers about the offerings of Local Coffee Brand. The study's findings indicate that digital marketing, along with conventional methods, has emerged as an effective communication tool for swiftly and cost-efficiently disseminating promotional messages to consumers compared to traditional media.